The Dark Side of Leadership: Exploring the Influence of Leaders’ Psychoticism Trait on Employee Emotional Well-Being Through Emotional Intelligence - Johar, Siti Sarawati; Md Nor, Noranifitri; Arwansyah Kirin (Journal of Social Transformation and Regional Development, 2026)
This conceptual paper examines the influence of psychoticism personality traits among organizational leaders on employee emotional well-being, emphasizing emotional management as a key component of emotional intelligence. Drawing on Hans Eysenck’s PEN model, the study explores how traits such as aggression, egocentrism, and lack of empathy in leadership can undermine employee self-esteem and psychological safety. Psychoticism is also linked to dark leadership traits including narcissism, machiavellianism, and psychopathy, which contribute to toxic leadership styles. The paper integrates Mayer and Salovey’s Four Branch Model of Emotional Intelligence to demonstrate how emotional regulation and empathy serve as protective factors against the adverse effects of dark personality traits. A synthesis of recent literature and empirical findings confirms the relationship between emotional intelligence, transformational leadership effectiveness, and organizational commitment. Practical implications include personality screening in leadership selection, emotional intelligence training, and the development of psychologically safe workplace cultures. In conclusion, emotionally intelligent leadership can counterbalance the effects of psychoticism and enhance employee motivation, emotional resilience, and organizational harmony.